Invitation ? RMCMI 1994 ? 1995 Board of Directors (Rocky Mountain Coal Mining Institute, 1994)
Kenneth M. Payne RMCMI PRESIDENT 1994-1995 on behalf of the RMCMI Board of Directors and Officers of The Rocky Mountain Coal Mining Institute cordially invites you and your family to attend the 91st Regular Meeting and Convention to be held June 25 thru 27, 1995 Crested Butte, Colorado